Analysis of the research text for the conflicting narratives on the issue of extravagance - Mohammadreza Pircheragh; Ali Zare charkhloo (اخلاق وحیانی, 2023)
The issue of extravagance is considered one of the important religious issues that deserves to be investigated from its various aspects. It is often viewed from a jurisprudential and moral perspective. Its legal prohibition has been mentioned in many verses and hadiths, and its moral ugliness seems clear from an intellectual perspective.From the point of view of the concept, extravagance is a very comprehensive concept and includes any extravagance in quantity and quality, frivolity, extravagance, and the like, from extravagance in the costs of living to any sexual deviation and the pursuit of power in society and even cruelty to oneself and all of these issues, despite being matters of jurisprudence, except They are also discussed in the field of social ethics.This topic is widely reflected in Shiite and Sunni hadiths, and what is very important about them is the presence of hadiths in hadith sources, biography books, and others. It is that, apparently, some matters in which excess and extravagance occur are excluded from the category of extravagance. The apparent meaning of this group of narrations contradicts other narrations in the chapter on extravagance, and also contradicts the lexical, legal, customary, religious and moral concept of extravagance.What follows in this article is an analysis of the research text of the narrations opposing extravagance, with a detailed and systematic explanation of those narrations, in a descriptive and analytical manner. From studying the text of these narrations, it becomes clear, first, that the imaginary views of the conflict on the issue of extravagance are divided into two parts: “hadiths that on the surface appear to exclude some issues and things from the subject of extravagance” and “hadiths about extravagance in charity and charitable deeds and...” Secondly: The existing conflict between the two categories of narrations mentioned is not a real and established conflict, and there is a possibility of a customary combination of these narrations.Therefore, this group of conflicting narrations - subject to the authenticity of the document - should be weighed with other evidences of textual research, and one should not make a general verdict on extravagance or lack of extravagance in some areas with a superficial and brief examination.